An Analysis of Structuralism in the Poetry 'Kangen' by W.S Rendra - Salsabila Yasmin Susilo; Warsiman; Jamila Wijayanti (Universitas Negeri Semarang, 2025)
This study analyzes the relevance between physical structure and inner structure in the poem Kangen by W.S. Rendra, found in a collection of poems entitled Empat Kumpulan Sajak bagian Malam Stanza. Using a qualitative descriptive approach, this study applies reading and recording techniques to analyze written data. Structural theory describes various structures of the poem, focusing on its physical and inner elements. Physical elements include the selection of connotative diction, figurative language such as metaphor, hyperbole, repetition, concrete words, visual imagery, and low rhythm or beat. In addition, typographic elements, such as the use of capital letters and the use of complete punctuation, are also examined. Meanwhile, the inner structure involves the feeling, tone, theme, and message contained in the poem. These two structures are interrelated and inseparable and provide depth to the poem's meaning. The interaction between physical and inner structures can arouse the reader's feelings so that they can fully understand and appreciate the poem's contents. Thus, the synergy between physical and inner structures contributes significantly to forming the overall meaning of the poem Kangen.